Outdoor Activities and Myopia on Junior High School Student in Rural Area of Bali - Ni Made Ari Suryathi; I Putu Budhiastra; Ariesanti Tri Handayani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2018)
Introduction and Aims. Refractive errors such as miopia, hyperopia and astigmatism in teenagers are common in Asian country nowadays. Gadget usage also influence the prevalence and incidence of refractive errors specially for miopia and astigmatism. Outdoor activities have positive impact to prevent miopia. The aim of this study is to report the role of outdoor activities as unique school program that could prevent refractive errors in Junior High School in rural area of Bali Method. This is analytic descriptive study with cross sectional approach of 231 Pekutatan II Junior High School students taken in December 2016. This school located in rural area; 35,3 km from Jembarana and 60,5 km from Denpasar, the capital city of Bali. The area of the school is about 1500 m2, where 70% of the land are still vacant to natural habitat and this school had their own garden area that being organized by the students themselves after school hours. This school do not have computer extra curriculum as well. Result. From 231 students there were only 14 students that have refractive errors consist of 5 boys and 9 girls, mostly aged 15 years. Six students (2%) were diagnosed as myopia and 8 students (3.4%) were diagnosed as compound astigmatism myopia. The length of gadget usage in this school were 1.66 hours and outdoor activities time were 4.78 hours per day. The hereditary factors of refractive errors were noted in 12 students (5 %). Outdoor activities associated with refractive errors in this study (p = 0.03). While time using gadget does not have an association with the refractive errors (p = 0.38). Conclusion. Rural area where the outdoor activities are still common have protective effect to prevalence of refractive errors in teenager.